2011
DOI: 10.1108/17410381111102199
|View full text |Cite
|
Sign up to set email alerts
|

Governance and social capital formation in buyer‐supplier relationships

Abstract: Purpose-Building social capital within buyer-supplier relationships is often associated with high performing supply chains. However, little research has examined the mechanisms by which social capital is formed. Our paper examines the effects of relational and contractual governance mechanisms on the formation of social capital under varying levels of demand and supply uncertainty. Approach-A conceptual framework is developed, grounded in the literature on supply chain management and social capital theory. Fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(57 citation statements)
references
References 105 publications
1
56
0
Order By: Relevance
“…Table 3 illustrates that the information accessed through SSC has a significant negative effect on the opportunistic behaviour of the exchange partners (β = -0.238 or 24 percent and t-value = -5.79) supporting hypothesis H1. Similar results were provided by the studies of Carey andLawson (2011), Lu (2007) and Mysen et al (2011) confirming that information access through the network structure mitigates the opportunistic behaviour of exchange partners. Okten and Osili (2004) and Ting, Chen, and Bartholomew (2007) explained that the network size helps to tap information in the external environment successfully and reduce information asymmetry.…”
Section: Pls-sem Resultssupporting
confidence: 76%
See 3 more Smart Citations
“…Table 3 illustrates that the information accessed through SSC has a significant negative effect on the opportunistic behaviour of the exchange partners (β = -0.238 or 24 percent and t-value = -5.79) supporting hypothesis H1. Similar results were provided by the studies of Carey andLawson (2011), Lu (2007) and Mysen et al (2011) confirming that information access through the network structure mitigates the opportunistic behaviour of exchange partners. Okten and Osili (2004) and Ting, Chen, and Bartholomew (2007) explained that the network size helps to tap information in the external environment successfully and reduce information asymmetry.…”
Section: Pls-sem Resultssupporting
confidence: 76%
“…Dyer (1997) empirically observed that information exchange between the exchange partners reduced information asymmetry. Thus, many scholars (Carey & Lawson, 2011;Gulati & Singh, 1998;Joskow, 1985;Lu, 2007) have provided empirical evidences supporting that the RSC has an effect on the reduction of the tendency for opportunistic behaviour of exchange partners due to exchange of information. Table 3 further shows that the CSC has a negative significant effect on opportunism.…”
Section: Pls-sem Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Wathne and Heide (2004) argue that where there is no governance exercised in upstream relationships it will negatively influence the manufacturer's ability to respond to uncertainty in the downstream market. Carey and Lawson (2011) too share a similar view when they say that the performance of the supply chain can be improved with the social capital built up through enhanced supplier relationships (Nahapiet and Ghoshal, 1998). The implication is that without mitigating the uncertainty in the relationships with the suppliers a firm is unable to meet the expectations of their customers (Carey and Lawson, 2011).…”
Section: Introductionmentioning
confidence: 97%